pertanggungjawaban pidana pejabat pembuat komitmen dalam hal pengadaan barang dan jasa dengan modus jual beli jabatan aparatur sipil negara provinsi banten - Fahmi Anugrah Putra; Romasindah Aidy, Widya (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2025)
One form of criminal act of corruption is irregularities in the process of procuring government goods/services which are detrimental to state finances or the state economy. These deviations generally occur because officials are negligent or careless in understanding and implementing the provisions of the laws and regulations. The Commitment Making Officer (PPK) is a very crucial position, this is because the PPK plays a role in every stage of procurement of government goods/services. Therefore, PPK competence must be given great attention not only in the field of procurement of goods/services.